Investigation of Fear and Anxiety After The Earthquake in Terms of Social Variables - Çetintaş, Ahmet (Fırat University, 2025)
ABSTRACT One of the negative effects caused by earthquakes is forcing people to fear and anxiety dilemma and so, this makes struggling with disaster harder. In this study, the fear and anxiety level of people in Malatya who got caught unprepared to a big disaster such as February 6 2023 Earthquake and their usual psychological traumas and the relationships of those fears with sociological variations has been studied. The study has been conducted quantitatively by a questionnaire technique. In this way, a research questionnaire consisted of 29 questions were applied to 400 people in July 2024. The datas that were analyzed by SPSS 21 programme were evaluated with Frequency, Crosstab, T-Test, and Anova. As a result of the research, it has been seen that the fear and anxiety level of earthquake victim participants were high and this fear and anxiety level can differentiate according to gender, age, education, income and marital status. It has been detected that women have more fear and anxiety than men and the ones whose incomes were low have more fear and anxiety than who weren’t. Also, the ones whose wives or husbands died and the ones who divorced have more fear and anxiety than singles and married ones.

Depremlerin neden olduğu olumsuz etkilerden birisi de insanlarda yoğun kaygı ve korku duygularının ortaya çıkmasıdır. Bu durum, afetle mücadeleyi ve başa çıkmayı zorlaştıran bir etki yaratır. Bu çalışmada, 6 Şubat 2023 depremlerine Malatya’da hazırlıksız yakalanan insanların, afet sonrasında korku ve kaygı düzeyleri ve genel anlamda psikolojik açıdan yaşadıkları travmalar; bu travmaların temel bazı değişkenlerle olan ilişkisi araştırılmıştır. Araştırma, nicel yöntemde anket tekniğiyle gerçekleştirilmiş ve Temmuz 2024’te 400 kişiye 29 soruluk anket uygulanmıştır. SPSS 21 programı ile analiz edilen verilere Frekans, Çapraz tablo, T-testi ve Anova ölçümleri yapılmıştır. Araştırma sonucunda depremzede katılımcıların kaygı ve korku düzeylerinin yüksek olduğu; bu kaygı ve korku düzeylerinin cinsiyet, yaş, eğitim, gelir ve medeni durum gibi değişkenlere göre farklılaştığı görülmüştür. Kadınların erkeklere, eğitim ve gelir seviyesi düşük olanların yüksek olanlara göre kaygı ve korku düzeylerinin yüksek olduğu tespit edilmiştir. Ayrıca eşi vefat edenlerin ve boşananların bekârlara ve evlilere göre daha çok kaygılı ve tedirgin oldukları tespit edilmiştir.
Deprem Sonrası Korku ve Kaygıların Bazı Değişkenler Açısından İncelenmesi
Keywords: Urban Sociology and Community Studies; Kent Sosyolojisi ve Toplum Çalışmaları; Sociology of Health; Sağlık Sosyolojisi; Sociology of Quality of Life; Yaşam Kalitesi Sosyolojisi; Sociology (Other); Sosyoloji (Diğer)